Interdependence as an I(-)deal: Enhancing job autonomy and distributive justice via individual negotiation - Severin Hornung; Jürgen Glaser; Denise M. Rouseau (Zeitschrift für Personalforschung (ZfP), 2010)
Drawing on the concept of idiosyncratic deals (i-deals), the study tests assumptions regarding interdependencies between individuals and organizations in determining work and employment conditions. I-deals are personalized arrangements individual employees negotiate with their employer. We suggest that workers use i-deals to make their jobs more intrinsically and extrinsically rewarding. Ex post negotiation is assumed to have positive effects on autonomy and distributive justice, which should mediate a positive relationship between i-deals and job satisfaction. Cross-sectional (N = 373) and longitudinal (N = 74) survey data support the hypothesized relationships. The potential of i-deals as a means for individualizing organizations and further research needs are discussed. – – Basierend auf dem Konzept der idiosyncratic deals (i-deals) werden wechselseitige Abhängigkeiten zwischen Organisationsmitgliedern und -strukturen in Form individueller Einflussnahme auf Arbeits-und Beschäftigungsbedingungen untersucht. I-deals sind personalisierte Bedingungen, die auf individuellen Aushandlungsprozessen und Übereinkünften zwischen einzelnen Beschäftigten und Vertretern der Organisation basieren. Es wird angenommen, dass i-deals von Mitarbeitern initiiert und ausgehandelt werden, um intrinsische und extrinsische Gratifikationspotenziale ihrer Arbeit zu erweitern. Positive Auswirkungen erfolgreicher Nachverhandlung (ex post i-deals) werden auf Autonomie und Verteilungsgerechtigkeit erwartet, von denen angenommen wird, dass sie zwischen i-deals und Arbeitszufriedenheit vermitteln. Hypothesen werden durch quer- (N = 373) und längsschnittliche (N = 74) Fragebogendaten unterstüzt. Potenziale und Grenzen individueller Aushandlung als Mittel zur Individualisierung von Organisationen sowie offene Forschungsfragen werden diskutiert.
Keywords: 330; idiosyncratic deals; individual bargaining; job autonomy; distributive justice; job satisfaction; cross-lagged panel analysis; Arbeitsbedingungen; Arbeitszufriedenheit; Verhandlungen; Implizite Kontrakte; Organisationsforschung